Synergistic model development for lean manufacturing implementation at small and medium enterprises in Malaysia - Yusoff, Mohd Shahrizan (2018)
Historically Lean Manufacturing (LM) is originally derived from Toyota Production System (TPS). The core functions of LM practices are to create high-quality products and to minimise non-value added (NVA) activities in a company. Although LM had successfully implemented in various large corporations around the world since the 1980s, however, the evidence of LM’s adoption in Malaysian Small and Medium Enterprise (SMEs) were rarely documented. Malaysian SMEs predominantly characterised by low volume, highly mixed product yield as well as limited shop floor management and human control processes. Therefore, the focal objective of this study was to develop a model based on LM’s philosophy to help Malaysian SMEs improving their competitiveness in manufacturing operations management by synergising or cooperation of the LM critical successful factors including the efficiency of production management and human resource development to create more positive impact on the sustainability of effective business management system. To achieve the objective of the study, three different research phases were integrated. The approaches cover methods of, research review, exploring the LM implementation in Malaysia using statistical inference and construction of Structural Equation Modelling (SEM) and industrial research in the real industry involving two SMEs in northern of peninsular Malaysia. The research review methods conducted by collecting qualitative research data, including observations and examination of documents to assess the impact of the implementation of the LM among the SMEs organisation. Then, for exploring the LM implementation among Malaysian SMEs, surveys with 250 sets of questionnaires were distributed. Quantitative data obtained with a response rate of 40% then was analysed by using descriptive and inferential statistics. Results of the descriptive statistical analysis show that most Malaysian SMEs provide positive feedback with the mean score above 3.00 against the proposed implementation of LM variables comprising elements of operations management efficiency, human resource development, and ii preservation of the business. The findings from SEM results also confirmed that the LM variables did affect the performance of SMEs significantly. Then, the final model called as Synergistic LM for Malaysian SMEs (SyncLM) was developed using SEM. Lastly, the SyncLM model has verified its reliability through the implementation framework in two case studies of SMEs show a high tendency for them to implement and incorporate elements of the concept of LM that this synergy concept. The results showed that SyncLM model has managed to reduce 6.85% production time and 18.25% product defects for the first case study. Positive results are also obtained from second case study where the SyncLM model has successfully reduced 9.7% production time and 4.2% of product defects. Additionally, over 80% of the satisfaction scores have been achieved by respondents comprising management and employees from both companies with the implementation capability and effectiveness of benefits derived from the implementation of this SyncLM model. Therefore, it can be concluded that the SyncLM was able to improve the sustainability of the business functions of Malaysian SMEs.